ANALYSIS OF THE ACTIVITY OF SCHEDULING THE DISTRIBUTION OF CPO (CRUDE PALM OIL) AND PKO (PALM KERNEL OIL) PRODUCTS AT PT. MITRA ANEKA REZEKI (MAR) - Siti Maulidia; Novira Kusrini; Dewi Kurniati (Fakultas Pertanian Universitas Tanjungpura, 2019)
ABSTRACTIndustry has a level of intense competition in the free market era, even at the distributor level. Consumers will feel satisfied with the service of distribution, if the product arrives on time, the right amount and the right quality. PT. Mitra Aneka Rezeki partners have a problem with the lack of inventory when there is an order and its distribution system, such as delivery time, the number and type of goods delivered to each company destination and the cost of goods distribution. Resulting in the occurrence of shortages or excess inventory in the company in question. This study aims to plan the scheduling of product distribution activities to be well coordinate and minimal distribution costs with the optimal number of shipments using the DRP method. DRP is a method for handling inventory procurement in a multi echelon distribution network. From the results of the research, the distribution of companies during 2017 was 144 shipments at a cost of Rp. 3.037.509.720,-., when appling the DRP method, distribution will only be carried out as much as 40 times at a cost of Rp. 2.928.412.580,-,resulting in a decrease in cost of Rp. 109.097.140,- or 3,6 %..Keyword : Aktivity, Distribution, scheduling